Bulat Okudzhava’s world of poetry - Kotlarek, Magdalena (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2011)
The author of the article investigates the motives that led Okudzhava to write his songs and poems. The article outlines a multitude of motifs used in Okudzhava’s poetry and gives a description and explanation of the major themes of his poems. The author also shows how those particular motifs determine the nature of the bard's writing in general.